ADULT DISTANCE EDUCATION AND LEARNING IN LIFELONG LEARNING - Rutkienė, Aušra; Trepulė, Elena (Acta Paedagogica Vilnensia, 2009)
The lifelong learning paradigm opens vast possibilities of returning to learning and flexible participation in learning for adults. This concept emphasizes modern learner-centered learning forms that allow adults to learn according to their possibilities, pace and timing. Effective application of distance learning and its elements in lifelong learning process remains to be an issue. The article presents results of a research about possibilities of distance learning application, including results of teacher and learner survey. The survey results include aspects of motivation for participation in distance learning, learning forms that are being used, the most burning issues and differences of teacher and learner attitudes. The survey results demonstrate that the elements of distance education are being employed through the paradigm of traditional learning as the most frequently used elements of distance education are provision of references or Internet sources. Teachers who work in the mode of distance education employ different teaching methods, but the most frequent is independent work, provision of information, development of independent skills, practical assignments. The major motivation for distance education is personal interest and convenience. The teacher respondents emphasized the importance of sufficient resources, especially human resources. The survey analysis has showed that the elements of distance education are the most often used in educational establishments and rather rarely in business enterprises and vocational training schools. Distance education in business is the target of the future and its success will depend on the accessibility and quality of these services.